2021
DOI: 10.3390/su13052507
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Accessible Serious Games for People with Dyslexia

Abstract: Dyslexia is a cognitive disorder that affects the evolutionary ability to read, write, and speak in people, affecting the correct learning of a large percentage of the population worldwide. In fact, incorrect learning is caused because the educational system does not take into consideration the accessibility parameters that people with dyslexia need to maintain a sustainable educational level equal to others. Moreover, the use of mobile devices, such as smartphones and tablets, has been deployed in education p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
16
0
2
Order By: Relevance
“…Additionally, as mentioned earlier, an immersive experience seems to have a real utility in reducing the psychological distance perceived by an individual. Despite the lack of descriptive studies on this subject, the use of serious games whose design "serves to improve skills, adapt to an environment, understand a phenomenon or better adhere to a message" [59] while maintaining the codes of video games, offers this possibility and is a mean of learning [60][61][62][63][64]. Serious games are distinguished into two categories: educational games where "the learning objective is implicit" and pedagogical games where "the learning objective is explicit" [65].…”
Section: The Development Of Ecological Awareness Using Immersive Medi...mentioning
confidence: 99%
“…Additionally, as mentioned earlier, an immersive experience seems to have a real utility in reducing the psychological distance perceived by an individual. Despite the lack of descriptive studies on this subject, the use of serious games whose design "serves to improve skills, adapt to an environment, understand a phenomenon or better adhere to a message" [59] while maintaining the codes of video games, offers this possibility and is a mean of learning [60][61][62][63][64]. Serious games are distinguished into two categories: educational games where "the learning objective is implicit" and pedagogical games where "the learning objective is explicit" [65].…”
Section: The Development Of Ecological Awareness Using Immersive Medi...mentioning
confidence: 99%
“…In the first case, the user is required to handle a device and apply a physical pressure to a surface to trigger events. Whereas, in the second case, [2], [4], [5], [7], [10], [11], [18], [22], [24], [25], [28], [30], [34], [45], [51], [53], [60]- [121] 79 Mobile devices [13], [16], [19], [26], [31], [36], [37], [39], [41], [43], [44], [59],…”
Section: Interaction Technologiesmentioning
confidence: 99%
“…Immediate feedback after actions can also be useful, as it could help the users knowing when they succeeded or failed and why, recognizing their errors, recovering strategies, reducing their frustration and increasing their motivation. To this purpose, multimodal feedback are often provided, through congratulation messages, hints or events, like objects disappearing if correctly selected or sounds of clapping hands to highlight the correctness of a given answer [4]- [6], [13], [20], [41], [43], [50], [57], [59], [106], [112], [125], [133], [162], [208], [210]- [212]. Finally, since the benefits of cognitive training might only be noticed in the long term, healthy competition is greatly appreciated as it can positively affect patients psychological well-being and promote social networking.…”
Section: Interaction Technologiesmentioning
confidence: 99%
“…It can be used as a tool to reinforce the teaching process and provide enriching learning contexts for its users [26]. Most children with learning disabilities can be successful in reading acquisition with the help of a tutor or a specialized teaching program [33]. Emotional support also plays an important role for these children while dealing with learning disabilities [33].…”
Section: Introductionmentioning
confidence: 99%
“…Most children with learning disabilities can be successful in reading acquisition with the help of a tutor or a specialized teaching program [33]. Emotional support also plays an important role for these children while dealing with learning disabilities [33]. Several studies have shown that children prefer playing a "fun" computer game than performing a "boring" exercise [34].…”
Section: Introductionmentioning
confidence: 99%